Peluang Wanita Bekerja Keluar dari Pasar Tenaga Kerja Setelah Menikah - Yeni, Isra; Marta, Joan; Satria, Doni; Adry, Melti Roza; Putri, Dewi Zaini; Sari, Yollit Permata; Akbar, Urmatul Uska; Putra, Hari Setia (Jurnal Ekonomi dan Pembangunan Indonesia, 2022)
Working after marriage is a dilemma for most women in Indonesia. This study estimates the probability of a working woman to exit the labor market after marriage. Using the Indonesia Family Life Survey (IFLS) data from the 2007 and 2014 waves, this study estimates a logit model on the probability of a working woman to exit the labor force. This study found that working in the formal sector is the most significant variable to encourage a working woman to leave the labor force. The policy recommendation of this study is reducing the opportunity costs of working for women in the formal sector